Species composition and distribution of Medusae (Cnidaria: medusozoa) in the Algerian coast between 2°e and 7°e (SW Mediterranean Sea) - KHERCHOUCHE, ALDJIA; HAFFERSSAS, AZIZ (Mediterranean Marine Science, 2019)
The composition and abundance distribution of the Medusae community of the Algerian coast (between 2°E to 7°E) were investigated during autumn 2014. Zooplankton sampling was performed in the upper layer (0-100 m) at 14 stations. Fourteen species related to Hydromedusae and Scyphomedusae were identified. The Hydromedusae populations were represented by Leptomedusae (5 species), Narcomedusae (3 species), Trachymedusae (3 species) and Anthomedusae (2 species). Some species such as Cirrholovenia tetranema and Cunina globosa were newly recorded at the sampling areas. The total abundance of Medusae was under 10 individuals.m-3. Maxima of concentrations (> 4 ind.m-3) were localized at the central coast between Bou Ismail (2.6° E) and Algiers (3.2° E) Bays. Here, the populations of Aglaura hemistoma and Liriope tetraphylla were dominant (≈ 40%). A quantitative variability was showed between two populations groups (Liriope tetraphylla) and (Pelagia noctiluca and Rhopalonema velatum) characterized respectively the central region and the eastern region. Their distributions were analyzed in relation to environmental parameters (temperature, salinity, and chlorophyll-a) and the interaction with Copepods prey.